Etodolac, A Preferential COX-2 Inhibitor, does not Inhibit Platelet Aggregation in a Randomized Placebo-Controlled Trial - Zoller Norbert; Gähler Anita; Degiacomi Priska; C Korte Wolfgang (Journal of Advanced Pharmaceutical Science And Technology, 2013)
To date, platelet aggregation studies have not been formally evaluated in persons receiving Etodolac, a preferential cyclooxygenase-2 (COX-2) inhibitor. Our purpose was to investigate the influence of Etodolac in therapeutic (analgesic) doses (300 mg every 12h) on platelet aggregation as compared to placebo in healthy volunteers. Platelet aggregation, the primary efficacy variable in this trial, was performed according to the Born method with platelet rich plasma; it was evaluated as maximal platelet aggregation induced by 3 substances (adenosine diphosphate (ADP), epinephrine, collagen); each of these substances was used at 3 different concentrations. No significant difference in platelet aggregation as assessed by Born aggregometry was seen in volunteers treated with etodolac or placebo. Etodolac - applied in regular analgesic doses to volunteers - does not show an inhibitory effect on platelet aggregation and therefore seems an attractive analgesic substance for the perioperative setting.
Keywords: Cox-2 inhibitor – Etodolac – perioperative analgesia – platelet aggregation